Kovačević protiv Bosne i Hercegovine: da li federalizam i konsocijacija imaju značaja? - Markovic, Goran (NBP. Nauka, bezbednost, policija, 2023)
The subject of the paper is the judgment of the European Court of Human Rights in the case Kovačević v. Bosnia and Herzegovina. The judgment is a reflection of the Court’s opinion on discrimination against particular groups of citizens who may or may not, depending on the approach and attitude, use their active voting right in the elections for the Presidency of Bosnia and Herzegovina and the House of Peoples of the Parliamentary Assembly. The novelty of this judgement is in the fact that the Court analysed the possibility of exercising active voting right while in previous cases it decided on discrimination against groups of citizens regarding the exercise of passive voting right.The judgement has to be criticised for several reasons and from several angles. The Court did not take into account the legal nature of the Presidency and the House of Peoples which led it to wrong conclusions regarding discrimination against. It only took into consideration that the Others as well as some segments of constituent peoples could not be represented in these institutions. However, this fact has already been contained in several other judgements. The novelty is that the Court has judged that a voter cannot exercise the active voting right since he/she cannot vote for his/her preferred candidate for his/her ethnic affiliation and/or Entity place of residence.The purpose of this paper is to challenge this view and particularly to oppose the attitude that the implementation of this judgement has to introduce the solution that Bosnia and Herzegovina has to become one electoral district.